2010
DOI: 10.1159/000321693
|View full text |Cite
|
Sign up to set email alerts
|

Is Prostate-Specific Antigen Surveillance Necessary in Men with Benign Prostate Pathology following Radical Cystoprostatectomy for Bladder Cancer?

Abstract: Background: Radical cystoprostatectomy (RCP) remains the gold standard for the treatment of muscle-invasive bladder cancer. There are limited data regarding the clinical impact and detection of PSA following complete prostatectomy or the need to monitor serum PSA in patients with benign prostate pathology at time of RCP. The purpose of our study was to analyze the postoperative PSA characteristics of men without prostate cancer who underwent a RCP for bladder cancer. Methods: The demographic, clinical and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Conversely, in patients who undergo RCP, removal of the prostate obviates surveillance for prostate cancer. 22 No randomized controlled trials have been conducted to date to compare prostate-sparing cystectomy versus RCP regarding oncologic and functional outcomes. Hautmann and colleagues reviewed organ preserving cystectomies in the past 15 years; their results showed higher rates of distant failure when compared to standard or nerve-sparing cystectomies, and the authors concluded such an approach was a step backwards in oncologic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in patients who undergo RCP, removal of the prostate obviates surveillance for prostate cancer. 22 No randomized controlled trials have been conducted to date to compare prostate-sparing cystectomy versus RCP regarding oncologic and functional outcomes. Hautmann and colleagues reviewed organ preserving cystectomies in the past 15 years; their results showed higher rates of distant failure when compared to standard or nerve-sparing cystectomies, and the authors concluded such an approach was a step backwards in oncologic efficacy.…”
Section: Discussionmentioning
confidence: 99%